Pengaruh Penggunaan Bahan Limbah Polimer Sebagai Campuran Aspal Modifikasi Terhadap Kinerja Marshall - Indah Handayasari; Irma Sepriyanna Sepriyanna; Dyah Pratiwi Kusumastuti (Sekolah Tinggi Teknik - PLN, 2020)
One of the polymer materials that can be a mixture of asphalt is Ethylene Vinyl Acetate, which is a material that is widely used in making toys and making footwear. This large amount of toys and footwear production waste has only become rubbish and has not been utilized optimally. Ethylene Vinyl Acetate polymers themselves belong to elastomeric polymers which have flexible properties such as rubber, smooth, flexible, resistant to low temperatures, are not easily cracked and are resistant to water. The use of polymer material as a mixture of asphalt has been widely carried out considering that asphalt modification with polymeric materials is known from several tests showing that it has better resistance to deformation and overcoming cracks, so that road construction can be produced more durable and can reduce maintenance and repair costs Street. In this study the use of Ethylene Vinyl Acetate waste on asphalt mixes has a pretty good effect, this is seen from the results of marshall tests that can meet the requirements.